Implementation Of Sharia Marketing Mix In Tirta Agung Tourism Sukosari Village Bondowoso Regency - Subagio, N. Ari; Mahardiyanto, Agus; Riansaputri, Hesti Dwi; Zulfikri, Robby Reza; Ariyanti, Rini (Institut Agama Islam Negeri Lhokseumawe, 2024)
This research aims to determine and evaluate the implementation of the Sharia marketing mix in Tirta Agung tourism, Sukosari Village, Bondowoso Regency. This type of research uses a descriptive qualitative approach with case studies. Researchers used primary data and secondary data obtained through interviews, observation and documentation. Data analysis techniques use data collection, data reduction, data display and conclusion drawing. Analysis of the validity of the data used is the triangulation technique. The research results concluded that the concept of implementing the tourism marketing mix for Tirta Agung, Sukosari Village, Bondowoso Regency uses sharia principles. By applying indicators to the 9P sharia marketing mix which consists of Product, Price, Place, Promotion, Process, People, and Physical Evidence, Promise, and Patience.